Pattern of Antibiotic Resistance in Salmonella sp. Bacteria Contaminating Fresh Faeces of Laying Hens in Kediri District, West Lombok Regency - Ramdani, Fitrah Akbar; Riwu, Katty Hendriana Priscilia; Kholik; Mbura, Yonanda Verawati Haslinda; Zakarias, Herdin Vanek (Universitas Atma Jaya Yogyakarta, 2024)
Antibiotic resistance has become a common problem in poultry farming in Indonesia. One of them is caused by improper use of antibiotics. This study aims to determine the pattern of resistance of Salmonella sp. isolated from laying hens to antibiotics. The samples used in this study were thirty samples of fresh faeces of laying hens from Kediri District, West Lombok Regency. The samples were isolated and identified through Gram staining and biochemical tests (indole, methyl red-Voges Proskauer, triple sugar iron agar, citrate, and urease), resulting in ten positive samples of Salmonella sp. The study continued with antibiotic resistance testing using disc diffusion or Kirby-Bauer methods. The antibiotics used in the study were aztreonam, ciprofloxacin, streptomycin, chloramphenicol, and tetracycline. The results showed that Salmonella sp. has been resistant to some antibiotics. The highest resistance levels are streptomycin and tetracycline at 50% (5/10), while the lowest is ciprofloxacin at 10% (1/10). Antibiotics that are still sensitive are aztreonam 90% (9/10) and chloramphenicol 100% (10/10). The findings of this study conclude that there is a pattern of antibiotic resistance in laying hens farms that can have a negative impact on human and animal health.